DEVELOPMENT OF ONLINE MENTAL HEALTH SUPPORTING GROUP TO REDUCE MENTAL BURDEN DURING COVID-19 PANDEMIC - Annette d’Arqom; Brihastami Sawitri; Zamal Nasution; Dimas Setyanto; Safira Nur Izzah; Ludy Diana Wiradhika; Rakha Achmad Maulana (Jurnal Layanan Masyarakat (Journal of Public Services), 2020)
COVID-19 pandemic affects all aspects of human life, not only health, but also economic, education, and daily activity. The sudden changes caused a mental burden for the majority of people. Moreover, the infodemic might increase the burden. Unfortunately, not all people aware of their mental health and with the negative stigma from the community lead the patient to hesitate for sharing and seeking help. Therefore, an anonymous online supporting group (www.laluibersama.com) is developed to increase awareness of mental health and provided the facility to share and to support users. This site consists of several basic information and articles regarding COVID-19, emphasizes on pharmacotherapy and mental health issues, sharing forum, and mental health calculator based on depression, anxiety, and stress scales (DASS 21). From the evaluation, 53.61% of users choose mental health calculators as the most favorite page, followed by article (29.90%), homepage (12.37%), and sharing page (4.12%). Most of the respondents agree that the mental health calculator is unique and useful, therefore can be used as a screening of mental health problems prior seeking health professional help. Taken together, mental health needs more attention in this pandemic due to the increasing burden, and the screening of mental health problems and sharing to alleviate the burden can be performed at www.lalui bersama.com. Pandemi COVID-19 memengaruhi semua aspek kehidupan manusia, tidak hanya kesehatan, tetapi juga ekonomi, pendidikan, dan aktivitas sehari-hari. Perubahan mendadak tersebut menyebabkan beban mental bagi sebagian besar orang. Apalagi, badai informasi bisa menambah beban. Sayangnya, tidak semua orang menyadari beban mental mereka, dan memiliki orang untuk berbagi dan peduli. Oleh karena itu, kelompok pendukung online anonim (www.laluibersama.com) dikembangkan untuk meningkatkan kesadaran akan kesehatan mental dan menyediakan fasilitas untuk berbagi dan mendukung antar pengguna. Situs ini terdiri dari beberapa informasi dasar dan artikel mengenai COVID-19 dengan penekanan pada farmakoterapi dan kesehatan mental, forum berbagi, dan kalkulator kesehatan mental berdasarkan skala depresi, kecemasan, dan stres (DASS 21). Dari evaluasi tersebut, 53.61% pengguna memilih kalkulator kesehatan mental sebagai halaman favorit, diikuti oleh artikel (29.90%), homepage (12.37%), dan halaman berbagi (4.12%). Sebagian besar responden setuju bahwa kalkulator kesehatan jiwa itu unik dan valid, oleh karena itu dapat digunakan sebagai skrining masalah kesehatan jiwa. Secara keseluruhan kesehatan jiwa perlu mendapat perhatian lebih dalam menghadapi pandemi ini karena beban yang semakin meningkat, dan pemeriksaan dini masalah kesehatan jiwa dan berbagi kekhawatiran dan pemikiran dapat dilakukan di www.lalui bersama.com.